"Agrobacterium yellow group" and Pseudomonas paucimobilis causing peritonitis in patients receiving continuous ambulatory peritoneal dialysis. Issue 11 (November 1985) - Swann, R A; Foulkes, S J; Holmes, B; Young, J B; Mitchell, R G; Reeders, S T
Abstract : Five cases of peritonitis occurred during continuous ambulatory peritoneal dialysis in which unusual yellow pigmented Gram negative bacteria were isolated in pure culture. Four of these isolates were identified as the so called "Agrobacterium yellow group." The remaining isolate was identified as Pseudomonas paucimobilis, an organism closely related to the Agrobacterium yellow group.